Sectional analysis of pendentive dome mosques during Ottoman era= Analyse sectionalle des mosquees a dome pendentif pendant l'epoque Ottomane - Sanusi, Ahmad Hassan; Mazloomi, Mehrdad; Spahic, Omer (Canadian Academy of Oriental and Occidental Culture, 2010)
This study analyses types of pendentive dome mosques based on their variations from sectional view of documented drawings. The scope of this study is limited to the mosques constructed in Ottoman period which refers to the pendentive dome mosque architecture. The methodology applies descriptive analysis to classify its variation. This analysis takes into account that the main dome plays important role in classifying the variation. There are 51 mosques selected for the case studies. The study found that five types of the pendentive dome mosques can be identified accordingly. The number, position and organization of the dome design become the determining factors that influence the categories. The analysis also finds that all main domes share similar position located at the center of the prayer hall. The number of main domes comprises two and three units in the third category and it has more than three units in fourth category whereas the number of main dome is not more than one unit in other categories. The dome with higher rank of category show higher quality in terms of aesthetical value leading to visual feeling of domination in section view. In overall, the rank of the mosque’s category besides corresponds to the level of its dome organization. The mosques in the higher ranked categories have more elaborated dome organization. This fits well with the logic of the hierarchy of importance to the corresponding category.